ANALYSIS OF REGIONAL INDUSTRIAL INNOVATION LEVEL AND COMPETITIVENESS (FOR EXAMPLE, TASHKENT REGION) - Sherkulovna, Batirova Nilufar (International Journal of Psychosocial Rehabilitation, 2020)
The article focuses on the development of a system of objective assessment of regional industrial activity and their impact on socio-economic infrastructure. It is recognized that the feasibility of resource development in the region is recognized in determining the innovative development strategy and innovative development strategies of the region. Analyzes the possibilities of preserving the existing industrial and technological potential in the process of innovative development of industry in Tashkent region. The conclusion lists the trends in the development of innovative products in the region.